Effects of footwear condition on maximal jumping performance - Harry, J. R.; Paquette, M. R.; Caia, J.; Townsend, R. J.; Weiss, L. W.; Schilling, B. K. (The Journal of Strength and Conditioning Research, 2015)
The purpose of this investigation was to examine the effects of footwear on kinetics and lower extremity electromyographic (EMG) activity during the vertical jump (VJ) and standing long jump. Fifteen men performed the 2 jump types in 3 footwear conditions: barefoot, minimal shoes, and cross-training shoes. Jump displacement and kinetic data were collected, along with EMG activity of the biceps femoris, medial gastrocnemius, peroneus longus, semitendinosus/semimembranosus, soleus (SOL), tibialis anterior, vastus lateralis, and vastus medialis. Subjective footwear performance and comfort were also assessed with a custom survey. No differences were found in jump displacement, peak ground reaction forces (GRF), countermovement and propulsive phase durations, vertical impulse, peak countermovement, or average propulsive EMG activity. Significant differences in peak propulsive root mean square EMG were found between barefoot and minimal shoes (p = 0.030) and minimal shoes and shod (p = 0.031) conditions for the SOL during the VJ, and for average countermovement EMG of the semitendinosus/semimembranosus during the VJ between barefoot and shod (p = 0.039). Moderate-to-large effect sizes (>0.59) were found between conditions for horizontal GRF, propulsive phase duration, average EMG amplitude, and duration of EMG activity during the countermovement. Participants reported higher comfort ratings when shod compared with barefoot and minimal shoes for both jumps. Participants also perceived better performance when shod compared with barefoot and minimal shoes for the VJ only. No acute differences in displacement were observed between barefoot, minimal shoes, and cross-trainer shoes during vertical and horizontal jumps. Some differences in muscle activation and timing seem to be present, and thus, training effects between footwear conditions should be examined. Footwear familiarization may prove beneficial, as acute increases in comfort seem unrelated to performance improvements.